Transient partial permeabilization with saponin enables cellular barcoding prior to surface marker staining. Issue 12 (1st October 2014) - Behbehani, Gregory K.; Thom, Colin; Zunder, Eli R.; Finck, Rachel; Gaudilliere, Brice; Fragiadakis, Gabriela K.; Fantl, Wendy J.; Nolan, Garry P.
Abstract Fluorescent cellular barcoding and mass‐tag cellular barcoding are cytometric methods that enable high sample throughput, minimize inter‐sample variation, and reduce reagent consumption. Previously employed barcoding protocols require that barcoding be performed after surface marker staining, complicating combining the technique with measurement of alcohol‐sensitive surface epitopes. This report describes a method of barcoding fixed cells after a transient partial permeabilization with 0.02% saponin that results in efficient and consistent barcode staining with fluorescent or mass‐tagged reagents while preserving surface marker staining. This approach simplifies barcoding protocols and allows direct comparison of surface marker staining of multiple samples without concern for variations in the antibody cocktail volume, antigen‐antibody ratio, or machine sensitivity. Using this protocol, cellular barcoding can be used to reliably detect subtle differences in surface marker expression. © 2014 International Society for Advancement of Cytometry